620.92 INVESTIGATION OF DRYING EFFICIENCY IN A SOLAR INSTALLATION WITH COMPOSITE POLYETHYLENE FILM DEPENDING ON THE PRODUCT THICKNESS: Solar dryer - Muxtarov, Dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article is devoted to studying the effect of the thickness of the slices and the type of transparent coating material on the efficiency of solar drying of eggplant slices. The experiments were conducted in a solar dryer coated with a functional ceramic-based composite polyethylene film (Composite) and a conventional solar dryer using a regular polyethylene film. The results of drying in the open sun were also compared. For the study, fresh eggplants were cut into 5 mm and 10 mm thick slices and dried in both devices under the same environmental conditions (solar radiation intensity, ambient temperature, relative humidity, wind speed). During the drying process, the weight of the eggplant slices, the temperature inside the drying chamber, and the relative humidity were continuously recorded. The results obtained showed that the drying efficiency depends on the product thickness and the drying method. For 5 mm thick eggplant, the Composite device was found to be the most efficient method, achieving the lowest final residual mass. For 10 mm thick eggplant slices, the open sun method achieved the highest efficiency